The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1984
DOI: 10.1016/s0735-1097(84)80257-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase image evaluation of patients with ventricular pre-excitation syndromes

Abstract: To localize bypass pathways, left and right ventricular regions were analyzed at rest by phase image analysis in 18 patients with ventricular pre-excitation syndromes. These were compared with image findings in 18 normal subjects. In each of 17 patients with pre-excitation, the site localized on electrophysiologic study correlated closely with the region of earliest ventricular phase angle. This site could be objectively separated from that in normal subjects in each of eight patients with an active left-sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Early on, phase analysis was used with equilibrium radionuclide angiography (15) and applied to the characterization of abnormal patterns of ventricular activation (16), including the diagnosis of bundle branch blocks (17,18). More recently, phase analysis has been applied to gated myocardial perfusion SPECT (MPS), in which global synchrony measures derived from countbased thickening (19) have been shown to correlate with tissue Doppler imaging-derived measures of intraventricular delay (20) and, in a preliminary study, to predict response to CRT (21).…”
mentioning
confidence: 99%
“…Early on, phase analysis was used with equilibrium radionuclide angiography (15) and applied to the characterization of abnormal patterns of ventricular activation (16), including the diagnosis of bundle branch blocks (17,18). More recently, phase analysis has been applied to gated myocardial perfusion SPECT (MPS), in which global synchrony measures derived from countbased thickening (19) have been shown to correlate with tissue Doppler imaging-derived measures of intraventricular delay (20) and, in a preliminary study, to predict response to CRT (21).…”
mentioning
confidence: 99%
“…Electrophysiologists have demonstrated that in some cases atrial stimulation close to the accessory pathway might result in electrocardiographic signs of pre-excitation. Recently, precontraction assessed by echocardiography (Molina et af., 1982) and phase imaging (Botvinick et al, 1984;Chan et af., 1983;Rakovec er af., 1983Rakovec er af., , 1984, has been found to be present even in the absence of delta waves in the electrocardiogram. Experience in this respect has been limited to a small number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Fourier analysis of nuclear angiograms was performed using the technique recently described in detail by Swiryn (1985) and by Dae and Botvinick (1984). In brief, each patient received 800-lo00 mBq of technetium-99m.…”
Section: Methodsmentioning
confidence: 99%
“…Rest, supine electrocardiogram (ECG)-gated anterior, best septal left anterior oblique, and left lateral planar images were acquired in 16 frames, before and after CRT, using a Forte camera (Philips Electronics, Inc.), processed by commercial software. LVS, LVE, SDLVØ, IVS, right ventricular (RV) S (RVS), right ventricular E (RVE), and SDRVØ were calculated, based on the phase image generated from the first harmonic fit of the ERNA time-activity curve displayed by standard laboratory protocols (11,14).…”
Section: Ernamentioning
confidence: 99%
“…Each parameter was calculated from the first harmonic phase histogram in the ventricular ROIs: SDLVØ, SDRVØ, IVS (difference between mean LVS and RVS), LVS, and LVE are defined mathematically elsewhere (11,14,15).…”
Section: Definitionsmentioning
confidence: 99%